Confronting environmental quality and societal aspects: an environmental Kuznets curve analysis for Indian cities. (2016) - Sinha, Avik; Bhattacharya, Joysankar
Ever-growing problems of environmental degradation can be attributed to the inequality scenarios arising from the prevalent socio-economic imbalances and two of the major inequalities for the case of India in this regard are inequality in energy intensity and economic inequality. In this paper, we have taken the ambient air pollution data for 139 cities in India for the duration of 2001-2013, where sulphur dioxide (SO2 ) and nitrogen dioxide (NO2 ) have been chosen as the major air pollutants. Based on the empirical evidence, it can be found that interactions between inequality and societal aspects have significant contributions towards determining environmental quality. The paper concludes that any environmental policy cannot function effectively unless it takes other developmental policies into consideration. Leaving socio-economic parameters aside, the enhancement of environmental quality can prove to be extremely difficult to achieve, the evidence of which can be found from an analysis of Indian cities.